INCLUSIVE PEDAGOGIES & PRACTICES OF ENGLISH FOR ACADEMIC PURPOSES (EAP) IN HIGHER EDUCATION (HE): A FOCUS GROUP STUDY - Bakogiannis, Angelos; Lorrimer, Susan; Papavasiliou, Evie (PT ANTIS INTERNATIONAL PUBLISHER, 2024)
This study investigates inclusive pedagogies and practices in English for Academic Purposes (EAP) within higher education (HE), addressing a critical gap in existing literature. Funded by BALEAP, the research employs a qualitative sequential exploratory design, incorporating nominal group technique and focus group discussions to capture diverse stakeholder perspectives. The study identifies key themes across micro, meso, and macro levels, providing comprehensive insights into best practices for fostering inclusive EAP teaching. At the micro level, recommendations include redefining needs analysis, implementing differentiated assignment briefs, challenging linguistic and cultural stereotypes, and promoting reflexivity among educators. Meso-level strategies emphasise decolonizing the curriculum, integrating EAP into disciplinary courses, enhancing collaboration between EAP and subject-specialist tutors, and investing in continuous professional development. At the macro level, the study highlights the necessity of providing additional resources, fostering top-down collaborations, and introducing Equity, Diversity, and Inclusion (EDI) initiatives. The findings underscore the importance of coordinated efforts among educators, institutions, and policymakers to advance inclusive teaching practices in EAP. This research contributes significantly to the discourse on inclusive education by offering actionable recommendations for enhancing the inclusivity of EAP programs in HE, ultimately aiming to create a more equitable and supportive learning environment for diverse student populations. The study's robust methodological approach and diverse participant representation ensure the reliability and relevance of its conclusions, paving the way for future research and policy development in this crucial area of higher education.